PE pipe : design and installations. (AWWA manual, 2020)
This manual provides both technical and general information to aid in the design, specification, procurement, installation, and understanding of high-density polyethylene (HDPE) pipe and fittings. Municipal and consulting engineers should use M55 in preparing plans and specifications for new HDPE pipe projects. This manual will help managers, technicians, and engineers to: Understand the engineering properties of polyethylene; Get key information on manufacturing, testing, and inspection, Obtain knowledge on the hydraulics of PE pipe; Understand working pressure ratings and external load design, Gain insight into transportation, handling, and storage best practices for PE pipe; Identify procedures for the installation, maintenance, and repair of PE pipe. This Second Edition includes extensive updates throughout with significant updates pertaining to installation, external loading, and soil characteristics. The section on trenchless installations has been overhauled and updated to reflect current practices. Updates pertaining to current PE resins have been included throughout the manual. New appendices on earthquake applications, case studies, pipe data, and model specifications have been added.